(untitled) (World Economics and Finance Bulletin, 2024)
Therefore, Covid-19 is one of the most difficult challenges facing innovative industries. It has imposed a new economic commitment, as it has placed its danger in the rapid spread of music. While the virus took three months to infect the first 100,000 people around the world, it only took 12 days to infect another 100,000, according to a report by the organization. Major global health: Covid-19 has dealt a strong blow to the global economy, and the weaknesses have already appeared in the macroeconomics of the developed and developing prospects, nor the economic and financial powers, especially since these countries may be significantly affected by the decline in prices in addition to the impact of other economic impacts as a result of the state of scientific closure, which is limited On the ability and effectiveness of Ali to support the employer at the time when it is needed most. Even now, with eight years to go, it is expected that economic initiatives for the Corona pandemic will be a long time ago, and whatever the case may be, it is extremely important to finance financing for the development of what is known as the (rescue package) that is still spreading from the effects of the crisis (to spread). Covid19 and the decline in various oil prices in light of the pandemic. The research addresses the problem of economic companies in Iraq being clearly affected by global changes extending to the decline in oil prices, and is effective in combating Corona in light of the decline of rescue programs for the fragile segment of society and planning financial and monetary policies in light of The revolution in oil prices in the global market and how to confront the complex economic impacts on the Iraqi economy as a result of investing in oil prices, as investors do in several analytical prescriptions. By reviewing the available data on economic activities, analyzing those, and explaining the economic impacts and addressing them, the researchers reached results, the most notable of which is the state of economic stagnation in Oil prices changed during the period 2019-2020, in which oil rentierism began for government revenues and the weakness of government rescue packages through fiscal and monetary policy controlled by the government and controlling the fragile rulers in Iraqi society